COMPLICATIONS OF TREATMENT FOR ACROMIOCLAVICULAR JOINT INJURIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article examines complications in the treatment of acromioclavicular (AC) joint injuries, including both common and rare cases. Emphasis is placed on the anatomical features of the joint, damage classification, and modern approaches to the prevention and treatment of complications. The advantages of contemporary diagnostic methods such as MRI and 3D imaging, as well as the effectiveness of minimally invasive surgical techniques, including arthroscopy and bioresorbable implants, are discussed. The importance of rehabilitation in preventing long-term complications, such as chronic instability and post-traumatic arthritis, is highlighted. Recommendations for optimizing medical care based on the latest advancements in traumatology and orthopedics are provided.